Time of a Thesis: Academic Marginalia; Or Postcards from the Road - Jagger, Susan; Trifonas, Peter Pericles (Canadian Journal of Education/Revue canadienne de l'éducation, 2019)
Postcards share with others the highlights of holidays, memories of places and events, and brief stories of experiences abroad. They hold the quick jottings to a friend back home, made while in a moment of rest and reflection on a train, at the beach, in a café. They are intimate artifacts, yet they are also public. Their text is available for anyone to read, exposed and vulnerable outside of the safety of a sealed envelope. The postcard reveals itself to all who choose to turn their gaze toward it, to read its signs, and meditate on its meanings. The following postcards written to “R,” to the reader—and in parallel dialogy with another text addressed to “S”—are a narrative invitation to travel on a reflective journey through academia, tracing the experiences of graduate studies in science education and curriculum studies, the external and internal barriers that bounded the navigation of the field, and the cartography of decisions that opened up possibilities for successes at the margins of the academy.